Penerapan Model Pembelajaran Kooperatif Picture and Picture untuk Meningkatkan Hasil Belajar Peserta Didik - erna fitriani (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
Abstract This study aims to improve science learning outcomes for class VII A students of SMPN 3 Kasihan through the picture and picture cooperative learning model. This is because students are less active in teaching and learning activities as well as low attention to learning material. This type of research is Classroom Action Research (PTK) with the research subject of class VII A students of SMPN 3 Kasihan for the 2018/2019 academic year, a total of 32 students. The implementation of the action was carried out in 2 cycles, each cycle consisting of 2 meetings. The instruments used are observation, documentation, and test. Observation is used to observe during the teaching and learning process, documentation to collect data and student test results, as well as test methods that are carried out at the end of each cycle which are useful for knowing the increase in student learning outcomes. The data analysis technique is in the form of descriptive qualitative. This study showed an increase in student learning outcomes KI 3 (knowledge) cycle I obtained a completeness level of 37.50%, cycle 2 increased to 100%, which means there was a significant increase of 62.50%. Whereas in KI 4 (skills) in cycle 1 the level of completeness reached 59.38% while in cycle 2 it was 90.62% which means there was a significant increase of 31.24%.   Keywords: Learning Outcomes, Picture and Picture.